Pelatihan Barista Untuk Siswa-Siswi Di SMK Al-Azhar Batam - Syafruddin Rais; Tito Pratama; Natal Olotua Sipayung; Ardiansyah Saputra; Dailami (JURNAL KEKER WISATA, 2024)
PKM Lecturer Activities About Barista Training is a program designed to provide participants with in-depth training in the skills and knowledge needed to become a skilled and professional barista. This training not only covers basic techniques in coffee making, but also advanced aspects such as latte art, knowledge of different types of coffee beans, and skills in serving coffee to customers to the highest standards. The main objectives of this training are. Mastery of Coffee Making Techniques: Teaches participants about basic techniques such as grinding coffee beans, choosing the right tools and machines, perfect espresso extraction, and milk steaming techniques. Latte Art Skills Development: Introduce and train participants in latte art which includes latte art, which is a technique for creating interesting patterns or images on the surface of coffee with milk. Knowledge about Coffee Beans: Educate participants about various types of coffee beans, processing processes, and how to choose the right beans to produce coffee with the best taste and aroma. Professional Customer Service: Prepares participants to be able to provide friendly and professional customer service, including how to communicate with customers and manage their expectations. Compliance with Hygiene and Safety Standards: Ensure that participants understand and implement high standards of cleanliness and safety in their daily operations, including sanitation of equipment and work areas. Barista training is usually held in a variety of formats, ranging from intensive workshops to more structured courses of varying duration. This program is aimed at individuals interested in starting a career as a professional barista, cafe owner, or anyone looking to improve their skills in the fast-growing coffee industry.